Incidence of post open appendectomy incisional hernia in Erbil City - Taher Barzinjy, Saman; Othman Habeeb , Hailah (Diyala Journal of Medicine, 2023)
Background: since acute appendicitis is the most common presenting diseases in the surgical emergency departments, Appendectomy regarded as a common emergency surgical procedure that is done by the surgeons in the general surgery specialty. The complication of an incisional hernia development after open appendectomy is rare, found in about 0.12% of the appendectomy operations; interstitial type of incisional hernia complication following open appendectomy surgery is extremely rare condition, small number of reports found to deal with the incisional hernia development at the site of appendectomy in a range of (0.4-0.7%). Objective: To assess the incidence of incisional hernia following open appendectomy in Erbil province – Kurdistan region- Iraq. Patients and Methods: This retrospective study involved 598 cases between the period of first of July 2015 to 30th of April 2020, the cases presented with features of acute appendicitis, after admission and complete history taking, surgical intervention (open appendectomy) has been done for all of them, follow up for the diagnosis of the post appendectomy incisional hernia development done throughout revising the files and ID s of the patients and contacting them or their close relatives via personal mobile numbers, others re-consulted us for any operation site discomforts, any patient with suspicion of operation site problems asked to return to the outpatient surgical room for follow up and excluding or confirmation of operation site incisional hernia. The patients followed up for about 2-3 years after the operation days and contacting period with the patients or their close relatives to exclude incisional hernia development at open appendectomy site took about 6 months. Results: Out of 598 cases included in this retrospective study, 286 cases were male and 312 cases were female, the ages ranged between 5 and 91 years old with a mean and Standard Deviation (SD) 24.13, the age group of up to 10 years old included 13 cases, 2nd decade age group included 258 cases, while the third age group (21 – 30 years old) was included 167 cases. Risk factors for development of incisional hernia assessed among all cases, 56.85% of all cases had at least one of the risk factors and the remaining 43.15% devoid of any risk factors, the risk factors distributed among constipation (19.4%), pregnancy among female patients (18.9%), followed by diabetes mellitus, chronic cough and heavy working occupations (4.85% ,4.52% and 3.34% respectively), and BPH and anemia with other immunocompromised risk factors made only about 5.8%, only three patients (0.5%) developed incisional hernia after open appendectomy. Conclusion: Post open appendectomy incisional hernia is rare in patients without risk factors of wound dehiscence, with minimizing the risk factors of incisional hernia and wound dehiscence, the incidence of open appendectomy wound incisional hernia can be minimized to lowest rate.